Analisis Rasio Profitabilitas Sebagai Alat Ukur Untuk Menilai Kinerja Keuangan Perusahaan Sektor Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia - Dea Angraini Anu; Selvi Selvi; Meriyana Franssisca Dungga (CV. ULIL ALBAB CORP, 2024)
Competition in the business world is increasingly competitive, so companies are required to be able to control business activities better than competing companies. The aim of this research is to determine the financial performance of telecommunications companies listed on the Indonesia Stock Exchange in terms of financial ratio analysis. The financial ratios used are profitability ratios. This type of research is descriptive quantitative research. The research data used is secondary data obtained from the Indonesian Stock Exchange. The results of this research can be seen from the calculation of profitability ratios in telecommunications sector companies listed on the Indonesian stock exchange for the 2020-2022 period with the net profit margin calculation showing good performance, return on assets showing poor financial performance, return on equity showing poor financial performance and gross profit margin shows very good financial performance.